A Qualitative Analysis of College Counseling Center Staff Experiences of the Utility of Dialectical Behavior Therapy Programs on Campus. Issue 1 (2nd January 2021) - Kannan, Divya; Chugani, Carla D.; Muhomba, Monicah; Koon, Kimberly
ABSTRACT: Dialectical behavior therapy (DBT) is an evidence-based practice for suicidal and self-injuring behavior with growing popularity in college counseling centers (CCCs). With the exception of a single, quantitative study, no research to date investigates how DBT is used in CCCs or what factors influence program implementation. We conducted qualitative interviews with 15 CCC staff that were delivering DBT programs in order to inform a more richly detailed understanding of the process of developing and implementing a DBT program housed in a CCC.